Superelastic shape memory alloy cables for reinforced concrete applications. (1st September 2017) - Mas, B.; Biggs, D.; Vieito, I.; Cladera, A.; Shaw, J.; Martínez-Abella, F.
Highlights: Relatively large-diameter Ni-Ti cables characterized for their use in RC members. Uniaxial tensile tests at different temperatures and loading rates performed. Bonding tests between the cable and conventional concrete carried out. The cables have been used to reinforce two small scale concrete beams. Modulus of elasticity should be increased by adjusting the alloy or heat treatment process. Abstract: The research on shape memory alloys (SMAs) has attracted a lot of attention in recent years for different structural engineering applications. In this paper the performance of relatively large-diameter Ni-Ti SMA cables is depicted for their use in reinforced concrete applications. The cable was characterized through a complete experimental program, including electrical resistance tests to determine the phase transformation temperatures, monotonic uniaxial tensile tests at different temperatures and loading rates, and cyclic tests to quantify the amount of strain ratcheting. Moreover, bonding tests between the cable and conventional concrete were performed. Lastly, the cable was placed inside real beam specimens to work as longitudinal reinforcement. The low modulus of elasticity of the SMA cables used here was a limiting factor that needs improvement, but the good strain recovery of superelastic SMA cable presents novel and untapped opportunities for its use as reinforcement in concrete.